Effect of Aspirin in Vivo and in Vitro on Plasma Cofactors of Platelet Aggregation - Okonkwo, P; Sise, H. S (Thrombosis and Haemostasis, 1971)
It was found that suspension of normal washed platelets in a media which had been incubated with aspirin, or was derived from subjects taking aspirin, resulted in decreased platelet aggregation with ADP. The media consisted of either normal platelet poor plasma, fraction I-0 or heated plasma. When the latter two media were used, both the heated plasma and fraction I-0 were modified by pre-treatment of the donor subjects with aspirin or incubation of each fraction with aspirin, and this modification was a time-dependent reaction taking 5 to 10 min to take place. Furthermore, washed platelets exposed to aspirin and then washed and resuspended showed a decreased response to ADP. This was also a time-dependent reaction. It is concluded that aspirin affects not only the platelet but also the cofactors of ADP-induced platelet aggregation.